(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. Natura del documento - 3. I destinatari della CO - 4. L’autonomia giuridica dei monasteri - 5. L’obbligo di aderire a una federazione - 6. La formazione comune obbligatoria - 7. Il rilassamento della clausura - 8. Qual è la mens legislatoris? An Analysis of the Instruction Cor Orans on Women’s Contemplative Life: Challenges and Perspectives ABSTRACT: This article is a commentary of Cor Orans, the Implementing Instruction of the Apostolic Constitution “Vultum Dei Quaerere” on Women’s Contemplative Life, published in 2018 by the Congregation for Institutes of Consecrated Life and Societies of Apostolic Life. This Instruction has the character of a real pontifical law, in many aspects disrupting the law which hitherto governed enclosed nuns. By constraining every Monastery to be part of a federation, which although presented as a communion structure, in fact resembles a genuine structure of government, the Instruction harms the autonomy of Monasteries. This mandatory federal setup goes hand in hand with a slackening of the enclosure, and will give rise to a decrease in religious observance. The article further proceeds to outline the mens legislatoris, found between the pursuit of communion and shortage management, and underlines the reductive and materialistic view of contemplative life exhibited by the document. Finally, the article underlines the determination with which the Dicastery intends to apply the new norms, a determination which shows little consideration for the principle of legality.